Romulus’ adytum or asylum? A New Exegetical proposal for De lingua Latina 5, 8 - Lazzerini, Federica (Ciceroniana On Line, 2017)
A long-standing debate surrounds Varro’s structure of etymology in four progressive levels in ling. 5, 8, whereby each level is connected to a different kind of analysis and applies to a different class of words. A cryptic and elliptic expression, in an almost certainly corrupted passage in the manuscript of the text, covers the fourth level in uncertainty and ambiguity. While some scholars have retained the transmitted Quartus, ubi est aditus et initia regis (“The fourth level is where lies the entrance and the origins of the king”), the majority of modern interpretation rather advocates the emendation of aditus in adytum (“sanctuary”) and reads the passage as a reference to diverse kinds of mysteric cults, embedding the fourth level of etymology in an esoteric frame. This paper brings forward the proposal that the passage at issue contains no allusion to the mysteries, but a reference to the partly historical, partly legendary episode of Romulus’ foundation of a “sanctuary” on the Capitoline Hill, open to all beseechers coming from all peoples and social statuses. This institution led to the formation of the first core of the Roman inhabitants and, subsequently, of the vernacular substrate at the basis of the Latin language; as such, this episode agrees with Varro’s interest and ideas. The hypothesis that the quartus gradus etymologiae is to be connected to Romulus’ asylum may be defended either by reading the word adytum with a brand-new meaning, or by proposing to emend the text (aditus > asylum), thus obtaining: Quartus, ubi est asylum et initia regis. Molto si è discusso sui quattro livelli progressivi secondo i quali Varrone struttura l’etimologia in ling. 5, 8; a ogni livello è associato un diverso tipo di analisi e si applica a una diversa categoria di parole. Una formulazione criptica ed ellittica, in un passo che nel manoscritto del testo è quasi certamente corrotto, avvolgono il quarto livello in una nube di incertezza e ambiguità. Se alcuni filologi hanno difeso il mantenimento del tradito Quartus, ubi est aditus et initia regis (“Il quarto livello è dove è l’ingresso e le origini del re”), la maggior parte delle interpretazioni moderne opta piuttosto per l’emendazione di aditus in adytum (“santuario”) e legge il passo come un riferimento a vari tipi di culti misterici, collocando il quarto livello etimologico in un quadro di esoterismo. Nel presente contributo, si avanza la proposta che nel passo in questione non vi sia alcuna allusione ai misteri, ma un riferimento all’episodio storico-leggendario della fondazione, da parte di Romolo, di un “santuario” sul Campidoglio, destinato all’accoglienza di supplici provenienti da ogni popolo ed estrazione sociale. Questa istituzione portò alla formazione del primo nucleo abitativo di Roma e anche, di conseguenza, del sostrato vernacolare alle origini della lingua latina; come tale, tale episodio converge con gli interessi e le idee di Varrone. L’ipotesi che il quartus gradus etymologiae alluda al santuario di Romolo può essere difesa o dando una nuova interpretazione al termine adytum, o proponendo un’emendazione testuale (aditus > asylum), che produca il testo Quartus, ubi est asylum et initia regis.